2020
DOI: 10.1093/gerona/glaa218
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Calcium β-Hydroxy-β-Methylbutyrate and Vitamin D3 Supplementation on Muscular Function in Older Adults With and Without Resistance Training: A Randomized, Double-blind, Controlled Study

Abstract: The primary aim of this study was to determine whether supplementation with calcium β-hydroxy-β-methylbutyrate (HMB) and Vitamin D3 (D) would enhance muscle function and strength in older adults. Older adults over 60 years of age with insufficient circulating 25-hydroxy-Vitamin D (25OH-D) levels were enrolled in a double-blinded controlled 12-month study. Study participants were randomly assigned to treatments consisting of: (a) Control + no exercise; (b) HMB+D + no exercise; (c) Control + exercise, and (d) HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
(68 reference statements)
2
18
0
Order By: Relevance
“…This doubleblind controlled 12-month study by Rathmacher et al found that HMB in combination with Vitamin D had a significant benefit on lean body mass and showed improvement in knee extension peak torque even with no exercise. Overall, their findings showed that even without exercise, the HMB+ Vitamin D supplemented group showed significant increases in functional outputs than those in controls [11]. Interestingly, HMB has also been shown to increase anabolic signaling [12].…”
Section: Clinical Evidence -Nutrition As An Orthopedic Treatment Toolmentioning
confidence: 95%
“…This doubleblind controlled 12-month study by Rathmacher et al found that HMB in combination with Vitamin D had a significant benefit on lean body mass and showed improvement in knee extension peak torque even with no exercise. Overall, their findings showed that even without exercise, the HMB+ Vitamin D supplemented group showed significant increases in functional outputs than those in controls [11]. Interestingly, HMB has also been shown to increase anabolic signaling [12].…”
Section: Clinical Evidence -Nutrition As An Orthopedic Treatment Toolmentioning
confidence: 95%
“…In the study by Bislev, et al [20], contrary to expectations, there was a significant 4% reduction in handgrip strength. On the other hand, at Rathmacher, et al's [33] clinical trial, supplementation with cholecalciferol, calcium and β-hydroxy-β-methylbutyrate (HMB) improved muscle strength and physical functionality even in participants not engaged in the exercise program. In Lee, et al's [27] study, cholecalciferol supplementation and resistance training enhanced muscle mass and reduced time to walk a standard course.…”
Section: Cholecalciferolmentioning
confidence: 99%
“…Consequently, strategies to maintain or increase muscle mass are crucial, especially in populations suffering from sarcopenia, obesity, or cachexia. Currently, resistance exercise per se or in combination with supplementation, for example, proteins, ω −3 polyunsaturated fatty acids, and vitamin D, is considered the primary intervention to overcome muscle wasting (Dalle et al, 2021; Rathmacher et al, 2020). Unfortunately, ageing, frailty, and disease can decrease the sensitivity toward anabolic stimuli such as resistance exercise, partly due to insulin insensitivity, inflammation, and inactivity (Dalle et al, 2017; Kumar et al, 2009; Morton et al, 2018; Reitelseder et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…the primary intervention to overcome muscle wasting Rathmacher et al, 2020). Unfortunately, ageing, frailty, and disease can decrease the sensitivity toward anabolic stimuli such as resistance exercise, partly due to insulin insensitivity, inflammation, and inactivity (Dalle et al, 2017;Kumar et al, 2009;Morton et al, 2018;Reitelseder et al, 2021).…”
mentioning
confidence: 99%